The Role of Public Utilities - Briggs, Robert (Maine Policy Review, 1991)
The regulation of public utilities in Maine continues to evolve in response to changing economic, political and social forces. Not only has the structure of regulation of the electrical and telecommunications industry seen dramatic changes in the past 20 years, but it also is certain the next decade will see equally fundamental changes. Maine Policy Review invited three key participants in Maine’s regulatory arena to interpret the changes of the past two decades and what future changes we can expect. This article provides the perspectives of Robert Briggs of Bangor Hydro-Electric.